Analisis Penggunaan Data Uji SPT Dalam Penentuan Daya Dukung Fondasi - Iwan Haryanto; Dendi Yogaswara (Institut Teknologi Garut, 2026)
SPT (Standard Penetration Test) test data provides detailed information about soil resistance and the distribution of soil strength at a given depth. According to SNI 02-1726-2012, soil layers that have SPT test values above 50 are hard soil layers. From the results of the literature study of soil investigation data in the field of the UPF (Functional Service Unit) Garut building construction at point BH-1, it was found that the soil layer with a hard consistency with an N-SPT value of 60 from the drilling surface to a depth between 0-4 m, then at a depth of 4 m with a category including hard soil, so in that case it can use the choice of shallow foundation type or deep foundation. Based on the calculation of the UPF Garut building structure with the help of SAP 2000, the maximum axial load acting is 5651.08 kN, the calculation of the bearing capacity of the deep foundation (bore pile) using the Reese and Wright method results in an allowable bearing capacity of 7199.02 kN with a maximum soil pressure of 6741.81 kN. Meanwhile, the calculation of the capacity of the shallow foundation (foot plate) using the Terzaghi and Peck method resulted in an allowable bearing capacity of 6599.8 kN with a maximum ground pressure of 1015.7 kN/m², although the capacity of the bore pile foundation is higher, the shallow foundation has an advantage in terms of cost efficiency and implementation time, given the strong soil characteristics at a depth of 4 meters.